2006
DOI: 10.1021/ma060778q
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Grain Boundary Morphologies in Lamellar Block Copolymer/Nanoparticle Blends

Abstract: Polymer-coated nanoparticle additives are shown to stabilize the formation of high-energy tilt and twist grain boundary structures in amorphous lamellar block copolymer/nanoparticle blends. The distribution of the particle additives within the grain boundary region depends on the level of perturbation of the equilibrium structure and presents analogies to previously described block copolymer/homopolymer blends. At small tilt angles (chevron grain boundary) the particle distribution is equal to the equilibrium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
84
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 25 publications
4
84
0
Order By: Relevance
“…Similar observations have been also made by Listak and Bockstaller in BCP/NP blend lamella systems. 38 It should be mentioned here, that in the rods prepared in the absence of AuNPs, the Y-or T-junction defects are found as well, but the number density of the defects is lower than that in the rods containing AuNPs. The increased defect density in the rods containing AuNPs indicates that the addition of particles might stabilize the formation of the Y-or T-junctions in the rods under our experimental conditions.…”
Section: Resultsmentioning
confidence: 79%
“…Similar observations have been also made by Listak and Bockstaller in BCP/NP blend lamella systems. 38 It should be mentioned here, that in the rods prepared in the absence of AuNPs, the Y-or T-junction defects are found as well, but the number density of the defects is lower than that in the rods containing AuNPs. The increased defect density in the rods containing AuNPs indicates that the addition of particles might stabilize the formation of the Y-or T-junctions in the rods under our experimental conditions.…”
Section: Resultsmentioning
confidence: 79%
“…22 The segregation of particle fillers within GB regions was argued to be driven by the associated relaxation of chains within the GB region to their equilibrium conformation and the resulting reduction of stored elastic energy. 22 Support for the proposed energetic stabilization of GB defects by means of particle segregation was provided by Thompson, who analyzed the formation of symmetric tilt GB structures in BCP/nanoparticle blend systems using a hybrid self-consistent field/density functional theory. 23 The segregation of particles within GB regions in BCP materials also confirmed earlier reports by Gido and coworkers, who noted a distinctive change of the morphology of high energy tilt GB structures in a lamellar BCP/homopolymer blend system as compared to the pristine BCP system.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The basic phenomenology of GB structures in BCP materials was first discussed by Gido and Thomas who classified and evaluated the various GB types associated with tilt and twist deformations of lamellar BCPs [6][7][8][9]. Subsequent experimental studies revealed the relevance of process parameters (such as the application of shear fields), molecular architecture, and composition on GB formation as well as the implications of GB defects on, for example, the permeability of BCP materials [10][11][12][13][14][15][16][17].Despite the abundance of GB defects and their demonstrated relevance on the physical properties of BCP materials, very little is known about the governing parameters that determine the formation of the various types of GB structures in BCPs or the evolution of GB structures during, for example, thermal annealing. One parameter that is of particular interest is the energy penalty associated with GB formation as it provides insight into both the mechanism and driving force of grain coarsening during annealing.…”
mentioning
confidence: 99%
“…The basic phenomenology of GB structures in BCP materials was first discussed by Gido and Thomas who classified and evaluated the various GB types associated with tilt and twist deformations of lamellar BCPs [6][7][8][9]. Subsequent experimental studies revealed the relevance of process parameters (such as the application of shear fields), molecular architecture, and composition on GB formation as well as the implications of GB defects on, for example, the permeability of BCP materials [10][11][12][13][14][15][16][17].…”
mentioning
confidence: 99%